A corrugated gradient mechanical metamaterial: Lightweight, tunable auxeticity and enhanced specific energy absorption. (July 2022) - Zhang, Hang; Chen, Pengwan; Lin, Gaojian; Sun, Weifu
Abstract: As an emerging field, mechanical metamaterials have brought new options for energy absorption. Herein, the corrugated wall mechanical metamaterial with unique deformation mechanism was designed and systematically studied. Due to the difference in the interaction mechanism between corrugated walls, the normal auxetic structures with different lateral wall thickness ( t l ) have two deformation modes: " contact mode " and " non-contact mode ". It has been found that the mechanical properties of the structure are widely tunable by simply increasing the t l of the structure: for normal samples, continuous gradient samples and symmetric gradient samples, the compression modulus can be increased by 35.5%, 27.8% and 40%, respectively. Additionally, the specific energy absorption of the proposed structure is significantly improved by employing continuous gradient and symmetric gradient design methods. The specific energy absorption of symmetric gradient samples increased by 30.6% ( t l = 0 . 80 mm ), 81.5% ( t l = 1 . 15 mm ) and 63.3% ( t l = 1 . 50 mm ) compared with the normal samples with the same t l . In addition, by further optimizing the normalized amplitude (h/L) of the symmetric gradient structure, the SEA can be further improved. This study can provide a reference for the relevant research of tunable energy-absorbing device. Graphical abstract: Highlights: The change in lateral wall thickness leads to contact mode and non-contact mode of the structure. The mechanical properties of the structure are widely tunable by tailoring the lateral wall thickness. The SEA of the structure is significantly improved by using continuous gradient and symmetric gradient design methods. The control mechanism of auxetic behavior is explained by simulation and experiment.